Delivery management of suspected or confirmed COVID-19 positive mothers - Chih Lin; Shih-Ming Chu; Jen-Fu Hsu; Chin-Chieh Hsu; Yao-Lung Chang; Reyin Lien; Shao-Wen Cheng; Ming-Chou Chiang (Elsevier, 2021)
The Coronavirus Disease-2019 (COVID-19) pandemic has brought catastrophic impact on the world since the beginning of December 2019. Extra precautionary measures against COVID-19 during and after delivery are pivotal to ensure the safety of the baby and health care workers. Based on current literature, it is recommended that delivery decisions be discussed between obstetricians and neonatologists prior to delivery, and designated negative pressure delivery rooms should be arranged for COVID person under investigation (PUI). During delivery, a minimal number of experienced staff attending delivery should don personal protective equipment (PPE) and follow the neonatal resuscitation program (NRP). Positive pressure ventilation is best used in a negative pressure room if available. At-risk babies should be transported in an isolette, and tested for COVID-19 in a negative pressure room soon after bathing. Skin-to-skin contact and breast milk feed should continue under certain circumstances. Although newborns with COVID-19 infections often present with symptoms that mimic sepsis and one third of affected patients may demand some form of respiratory support, short-term prognoses are favorable and most recover within two weeks of symptoms onset. In this article, we will further elaborate on topics covering timing and mode of delivery, antenatal steroid, vertical transmission, delivery room management, airway management, transport, testing and isolation after birth, skin-to-skin contact, breast milk feeding, clinical features, outcomes, and discharge plans. In addition, we also share our experiences of encountering neonates born of suspected COVID-19 positive mothers.